The Oxfordshire mental handicap register. Issue 6266 (7th March 1981) - Elliott, D; Jackson, J M; Graves, J P
Abstract : A total of 2027 moderately or severely mentally handicapped people in Oxfordshire considered likely to require special services at some time have been identified for the Oxfordshire Mental Handicap Register. Prevalence rates for those aged 5 to 14 years are estimated to be 3.9 per 1000 home population and 4.14 per 1000 total population when hospital residents are included. Entry criteria are less strict than in other registers, however, and people are identified by general practitioners, health visitors, and hospital staff as well as through the more usual sources. The register is already proving useful when planning and providing services to those in need.